Self-Regulation Learning and Self-Awareness in The Classroom - Mikhael Klemens Kedang; Setya Yuwana; Hendratno; Suhartono (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The purpose of the study is determined research trends related to self-regulation learning and self-awareness in the classroom. This finding carried out in October 2022 by conducting Pop from the Scopus data bases using Bibliometric VoSviewer analysis in RIS format which resulted in Network Visualization, Overlay Visualization and Density Visualization. Based on the results of the analysis, it is necessary to increase student competence in various aspects, including research using a mix method, the relationship between self-regulation learning and self-awareness reviewed in a social-humanities manner, and can be applied to every level of education.